2011
DOI: 10.1007/s00441-011-1129-2
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and adult isoforms of XLAP2 form microdomains associated with chromatin and the nuclear envelope

Abstract: Laminin-associated polypeptide 2 (LAP2) proteins are alternatively spliced products of a single gene; they belong to the LEM domain family and, in mammals, locate to the nuclear envelope (NE) and nuclear lamina. Isoforms lacking the transmembrane domain also locate to the nucleoplasm. We used new specific antibodies against the N-terminal domain of Xenopus LAP2 to perform immunoprecipitation, identification and localization studies during Xenopus development. By immunoprecipitation and mass spectrometry (LC/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 36 publications
(51 reference statements)
4
20
0
Order By: Relevance
“…FL-LBR co-localized to a large extent with nuclear lamin B, but its distribution pattern of was distinct from that of BiP (a luminal protein of the ER) and Nup84/107 (a marker of the NPC) (Fig 1B). In addition, the eGFP fusion protein formed closely spaced microdomains, similar to those identified in previous studies using specific antibodies [16,35]. These raft-like structures, which had contour lengths from 300–600 nm, were readily detectable by both conventional and super-resolution (STED) light microscopy (Fig 1A, detail ).…”
Section: Resultssupporting
confidence: 80%
“…FL-LBR co-localized to a large extent with nuclear lamin B, but its distribution pattern of was distinct from that of BiP (a luminal protein of the ER) and Nup84/107 (a marker of the NPC) (Fig 1B). In addition, the eGFP fusion protein formed closely spaced microdomains, similar to those identified in previous studies using specific antibodies [16,35]. These raft-like structures, which had contour lengths from 300–600 nm, were readily detectable by both conventional and super-resolution (STED) light microscopy (Fig 1A, detail ).…”
Section: Resultssupporting
confidence: 80%
“…In X. laevis , there have been five cDNA sequences identified that are presumably translated into three different LAP2 proteins discovered so far, ω, β, and γ (Gant et al 1999 , Lang et al 1999 , Lang and Krohne 2003 , Chmielewska et al 2011 ). The Xenopus LAP2β (66 kDa somatic polypeptide) is the only one found in adult animals, whereas two other isoforms, ω and γ (86 and 40 kDa), are present in oocytes and eggs and are downregulated during embryogenesis (Chmielewska et al 2011 ). The N-terminal common fragment of XLAP2, when added to the in vitro nuclear assembly reaction, inhibits chromatin decondensation and nuclear growth similarly to the human LAP2β N-terminal fragment (Gant et al 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The location of the nucleus is precisely determined within the cell and its disruption may lead to serious dysfunction and decrease in cell viability [48, 140]. This may be exemplified by the phenomenon occurring in syncytial muscle cells in which the majority of nuclei are lined up separately beneath the plasma membrane whereas a small, distinctive population is clustered beneath the neuromuscular junction.…”
Section: Nucleus Positioningmentioning
confidence: 99%